Effect of Mutations Induction on Vegetative and Generative Characters of G16 Rice (Oryza sativa L.) - Ni Wayan Sri Suliartini; Shinta Adekayanti; Anak Agung Ketut Sudharmawan; I Gusti Putu Muliarta Aryana (Postgraduate, University of Mataram, 2023)
The aim of this research was to identify the vegetative and generative characters of G16 rice mutants due to gamma-ray irradiation. The experiment was conducted in Saribaye Village, Lingsar District, West Lombok Regency. The experimental design used was an Augmented Design, using three comparison plants, namely the G16 line (parent), Inpago Unram 1 variety, and IPB 3S variety. The four mutant populations tested were mutant doses of 200, 300, 400 and 500 Gy. The results showed that the induction of gamma ray mutations affected the character of plant height, flag leaf angle, flowering age, panicle length, number of filled grains per panicle, harvest age, and grain weight per clump. Comparison plants and mutant plants showed an interaction on all observed characters, except the number of total tillers and the number of productive tillers. Wide genetic diversity was shown by all characters, except flag leaf angle, total tiller number, weight of 100 grains, and weight of empty grain per clump. High heritability was obtained on the character of plant height (0.97), flag leaf angle (0.74), flowering age (0.99), number of productive tillers (0.57), panicle length (0.86), number of filled grain per panicle (0.92), number of empty grains per panicle (0.55), age at harvest (1.00), and weight of 100 grains (0.99).